FOSTER PARENTS' STATE OF MIND WITH RESPECT TO ATTACHMENT: CONCORDANCE WITH THEIR FOSTER CHILDREN'S ATTACHMENT PATTERNS AT 2 AND 3 YEARS OF AGE. Issue 4 (5th June 2014) - Jacobsen, Heidi; Ivarsson, Tord; Wentzel‐Larsen, Tore; Smith, Lars; Moe, Vibeke
ABSTRACT The present study investigated the possible differences between foster and comparison parents' state of mind with respect to attachment, and the concordance between caregiver state of mind and child attachment classifications among 60 foster children, all placed before the age of 2 years, as well as 42 comparison children. Caregiver state of mind was measured when the children were 2 years old (Time 1) while child attachment classifications were assessed at age 2 and again at age 3 years (Time 2). The associations between foster children's attachment, age at first and final placements, number of placements, and reasons for placement also were investigated. Descriptive analyses, including cross‐tabulations, and independent sample t tests were used. The results showed that the majority of the foster parents had an autonomous state of mind, and no significant group difference between foster and comparison parents was identified. At both time points, most foster children who were classified as secure had autonomous foster parents, as also was the case for the comparison children. The present results are encouraging, suggesting that placing foster children with autonomous foster parents early in life may help them to remain secure over time. Furthermore, focusing on the recruitment of autonomous foster parents is important when working with young foster children.